Distance Learning Implementation Strategies Forhigh School In Indonesia - Ahmad Cucus; Yuthsi Aprilinda (Bandar Lampung University (UBL), 2013)
Distance learning or e-learning to be one of the world's most popular method of learning, this is because e-learning allows a student to learn anywhere and at any time, but the application of e-learning can’t be implemented well in Indonesia, this is because the policy of face-to-face in classroom and obstacles to the facilities and high cost.From some of the constraints faced emerging a prototype of the concept of learning that combines face-to-face and distance learning, known as blended learning, combined with mobile learning facilities intended for distance learning more accessible for students and teachers, just use mobile phones or smartphones students and teachers can make learning easier, cheaper, and is not limited to space and time.